2005
DOI: 10.1096/fj.04-2974fje
|View full text |Cite
|
Sign up to set email alerts
|

Response of apolipoprotein E*3‐Leiden transgenic mice to dietary fatty acids: combining liver proteomics with physiological data

Abstract: Dietary fatty acids have a profound impact on atherosclerosis, but mechanisms are not fully understood. We studied the effects of a saturated fat diet supplemented with fish oil, trans10,cis12 conjugated linoleic acid (CLA), or elaidic acid on lipid and glucose metabolism and liver protein levels of APOE*3 Leiden transgenic mice, a model for lipid metabolism and atherosclerosis. Fish oil lowered plasma and liver cholesterol and triglycerides, plasma free fatty acids, and glucose but increased plasma insulin. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 64 publications
3
82
0
Order By: Relevance
“…The suspected increase in ␤-oxidation rates would explain the lower levels of plasma triglycerides and free fatty acids as well as hepatic triglycerides in the mice after fish oil consumption. The increase in ␤-oxidation caused by trans10, cis12 CLA consumption was however indicative of the development of insulin resistance, since levels of plasma and hepatic triglycerides, as well as plasma ␤-hydroxybutyrate and plasma insulin were significantly increased (de Roos et al, 2005a).…”
Section: Dietary Fatty Acids and The Hepatic Proteome: Fish Oil Tranmentioning
confidence: 97%
See 2 more Smart Citations
“…The suspected increase in ␤-oxidation rates would explain the lower levels of plasma triglycerides and free fatty acids as well as hepatic triglycerides in the mice after fish oil consumption. The increase in ␤-oxidation caused by trans10, cis12 CLA consumption was however indicative of the development of insulin resistance, since levels of plasma and hepatic triglycerides, as well as plasma ␤-hydroxybutyrate and plasma insulin were significantly increased (de Roos et al, 2005a).…”
Section: Dietary Fatty Acids and The Hepatic Proteome: Fish Oil Tranmentioning
confidence: 97%
“…How various dietary fatty acids can differentially affect hepatic protein expression became clear when we compared the effects of three dietary fatty acids -fish oil, trans10,cis12 CLA and elaidic acid -on plasma and liver metabolites and hepatic proteins in ApoE*3-Leiden transgenic mice (de Roos et al, 2005a). These mice are a model for lipid metabolism, insulin resistance and atherosclerosis that are sensitive to changes in many components of the diet (van Vlijmen et al, 1994;van Vlijmen et al, 1996;van Vlijmen et al, 1998).…”
Section: Dietary Fatty Acids and The Hepatic Proteome: Fish Oil Tranmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppose that the APOE3-Leiden mice are fed with different fat levels in their nutrition [81,82]. Upon these different levels, they develop atherosclerosis in a severity related to some extent to the fat load.…”
Section: Connectivity and Modalitymentioning
confidence: 99%
“…Both CLA-rich diets contained 0.6% (w/w) cis-9 trans-11 CLA. Fasting plasma biomarkers of insulin sensitivity were measured and changes in protein expression in skeletal muscle, hepatic and epididymal adipose tissues were determined using two-dimensional gel electrophoresis and MS (2) .The CLA-fed mice were equally protected from the metabolic syndrome compared with the control, as shown by significant decreases of 30-50 % in plasma insulin (P < 0.05), glucose (P < 0.05), NEFA (P < 0.05), TAG (P < 0.05) and IL-6 (P < 0.05) and an increase of 34 % in plasma adiponectin (P < 0.05). Proteomic analysis indicated that 134, ninety-two and forty-three proteins, including post-translationally modified isoforms, were significantly altered (P < 0.05) in the skeletal muscle, hepatic and adipose tissues respectively of CLA-fed mice.…”
mentioning
confidence: 99%